EMERGENCY PREPARATION OF THE POPULATION - Guliyeva Ulviyya Ingilab gizi (Foundations and Trends in Research, 2025)
. Emergencies occur as an inevitable consequence of natural, man-made and social events at the stages of development of human society. High-level preparedness of management bodies and forces is of great importance for the prevention and elimination of the consequences of these events. In modern times, the emergency system is considered an integral part of state security, and the efficiency of the management process in this area directly affects the protection of people's lives and property. Purposeful and systematic organization of civil defense measures serves to reduce the negative consequences of emergencies and ensure the safety of the population. The interaction of management bodies, rescue forces and public organizations in this area is an important guarantee of the stability of society. Civil defense education plays an important role in increasing the life and safety knowledge of not only professional rescue and security bodies, but also university students. The implementation of special programs in this area ensures that the younger generation acts promptly and correctly during emergencies